A patient with peripheral demyelinating neuropathy, central dysmyelinating leukodystrophy, Waardenburg syndrome, and severe hypoganglionosis associated with a novel SOX10 mutation. Issue 5 (21st April 2018) - Akutsu, Yuko; Shirai, Kentaro; Takei, Akira; Goto, Yudai; Aoyama, Tomohiro; Watanabe, Akimitu; Imamura, Masatoshi; Enokizono, Takashi; Ohto, Tatsuyuki; Hori, Tetsuo; Suzuki, Keiko; Hayashi, Masaharu; et al.
Abstract : In this report, we present the case of a female infant with peripheral demyelinating neuropathy, central dysmyelinating leukodystrophy, Waardenburg syndrome, and Hirschsprung disease (PCWH) associated with a novel frameshift mutation (c.842dupT) in exon 5, the last exon of SOX10 . She had severe hypoganglionosis in the small intestine and entire colon, and suffered from frequent enterocolitis. The persistence of ganglion cells made both the diagnosis and treatment difficult in the neonatal period. She also showed hypopigmentation of the irises, hair and skin, bilateral sensorineural deafness with hypoplastic inner year, severe demyelinating neuropathy with hypotonia, and diffuse brain hypomyelination. The p.Ser282GlnfsTer12 mutation presumably escapes from nonsense‐mediated decay and may generate a dominant‐negative effect. We suggest that hypoganglionosis can be a variant intestinal manifestation associated with PCWH and that hypoganglionosis and aganglionosis may share the same pathoetiological mechanism mediated by SOX10 mutations.